PERAN COURT OF ARBITRATION FOR SPORT DALAM MENANGANI KASUS RASIS DAN DISKRIMINASI DALAM SEPAKBOLA DI EROPA - Zul Asri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to understand the role of Court of Arbitration for Sport(CAS) in mediating racist dispute and discrimination in European football.Racism and discrimination is a classic concern in the universe., FIFA thenarranged to punish racism violence in statute. This also followed by UEFA’sdisciplinary regulations. According to UEFA statutes, every action done by eitherplayers, team official, or supporter is responsibility of the club, including racismconduct. However, member association and team do not necessarily accept thesanction imposed. To resolve the dispute, UEFA should make Alternative DisputeResolution (ADR) especially mediation and arbitration provided for professionalplayer. UEFA should address the dispute about racism to CAS to protect UEFAinterest in keeping partnership with member association.This research applies descriptive qualitative method and literature tounderstand the role of Court of Arbitration for Sport.Moreover, this also usepluralism perspective which states that non governmental actor is the mostinfluential in international relations. Besides, in pluralism, race is part ofplurality.Court of Arbitration for Sport roles to adjudicate and punish racismconduct and discriminative behavior in European footballusing arbitration withinthe family of sport. This can be seen from the following indicators such as role ofCAS in adjudicating racism violence done by supporter of PSV Eindhoven fromNetherland towards Arsenal FC player, Thierry Henry that took place in PhilipsStadium in UEFA Champions League 2002, moreover, Court of Arbitratin forSport also adjudicated racism violence between Hungarian Football Federationwith FIFA, where Hungarian national team supporter was singing anti-Semitismchants during the match against Israel national team.Keyword : Racism, sanction, ADR, interest, pluralism, adjudicative